Systematic Literature Review of Renewable Energy Concepts in High School Physics - Anasya Astiananda Isdayanti; Khusaini Khusaini Khusaini; Ahmad Taufiq Taufiq (Berkala Ilmiah Pendidikan Fisika, 2026)
Renewable energy has become a strategic topic in high school physics education due to its relevance to energy transition, technological development, and sustainability issues. This study aims to systematically review how essential physics concepts are applied, what instructional approaches are used, and how renewable energy education is integrated into high school physics curricula. A Systematic Literature Review (SLR) was conducted following PRISMA procedures, including identification, screening, eligibility assessment, and qualitative synthesis. A total of 210 articles were identified from three databases (Scopus, Web of Science, and Google Scholar) for the period 2021–2025. After duplicate removal and eligibility screening, 15 empirical studies met the inclusion criteria and were analyzed. The synthesis indicates that the dominant physics concepts addressed include energy conservation, energy conversion, electrical power, and system efficiency, typically contextualized through solar panels, wave energy, and alternative energy systems. In terms of pedagogy, approximately two-thirds of the studies employed Project-Based Learning (PBL), frequently integrated with STEM or STEAM approaches. More than half incorporated digital media such as e-worksheets, digital modules, augmented reality (AR), or interactive simulations to support conceptual visualization. The findings also reveal a growing alignment between renewable energy instruction and Education for Sustainable Development (ESD), particularly in fostering energy literacy and environmental awareness. Overall, renewable energy functions not only as contextual content but also as a conceptual and pedagogical bridge connecting physics principles, engineering design, and sustainability education. However, most studies focus on short-term instructional outcomes, with limited longitudinal evidence regarding sustained improvements in students’ energy literacy. Future research should expand cross-context implementation and examine long-term curricular integration of renewable energy within physics education.